Implementasi Aplikasi E-Menu Di Cafe Coffee Time Berbasis Android - Irawan, Devi; Fitriyani, Fitriyani; Wahyuningsih, Delpiah; Yanuarti, Elly; Andrika, Yuyi; Mayasari, Melati Suci (JATISI, 2024)
A coffee shop is a place where drinks and food orders are served, and a coffee shop is also a center of social interaction where people can gather, talk, write, read, joke or just spend time. Ordering is an activity carried out by consumers before making a purchase. To achieve customer satisfaction, a company must have a good ordering system. The research method used in this research adopts information gathering methods, namely observation methods, interview methods and library research methods. Mean while, for software development using the Prototype method. Currently, Coffee Time is experiencing difficulties in serving orders and is still using records that have not been computerized or is still using a manual system. Shoppers have to wait too long to order food, and it is difficult for waiters to record orders manually on paper. Recording orders manually is less efficient in terms of time. Therefore, to achieve customer satisfaction in placing orders, an Android-based E-menu application was designed at the coffee time cafe. So this research produces an Android-based E-menu application at the coffee time café that suits your needs and is well structured.